Galileo Satellite System and Signal Structure - Pirti, Atinc; Hosbas, Ramazan Gursel; Senel, Burak; Koroglu, Mehmet; Bilim, Serdar (Geomatik Journal, 2021)
Global positioning systems can be described as revolution today. These systems can be used in determining the approximate location of any object, navigating the means of transportation, in many measuring processes and in many areas that will make life easier. As a result of the three-dimensional space shortcut method with very precise time information, location information can be estimated with high accuracy and fast processing times. Global Positioning System (GPS), GLONASS (Globalnaya Navigatsionnaya Sputnikova Sistema) systems are actively used worldwide. In addition to these two systems, the GALILEO satellite system plans to serve many areas civilianly. In this study, the features of the GALILEO, its signals, the stages of its emergence, the differences between other systems and why it is needed.
Keywords: Galileo; GPS/GNSS; Satelite components; Signal structure; Geology; Remote Sensing